2018
DOI: 10.1111/trf.15108
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐selected platelets for platelet refractory patients with HLA antibodies: a single‐center experience

Abstract: BACKGROUND Platelet refractoriness due to HLA immunization represents a problem in transfusion management of thrombocytopenic hematology patients. Refractory patients can be managed by HLA‐selected platelet transfusions, but the optimal matching strategy is debated and how the degree of HLA mismatch influences transfusion outcome is poorly studied. STUDY DESIGN AND METHODS We studied 32 hematology patients who received 142 matched platelet units between 2007 and 2016. Four matching strategies were compared: 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
2
27
1
Order By: Relevance
“…Several articles have reported the effectiveness of HLA‐matched PLTs . Currently, the sensitivity and specificity of virtual cross‐match analysis has undergone remarkable progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several articles have reported the effectiveness of HLA‐matched PLTs . Currently, the sensitivity and specificity of virtual cross‐match analysis has undergone remarkable progression.…”
Section: Discussionmentioning
confidence: 99%
“…17 Several articles have reported the effectiveness of HLAmatched PLTs. 5,[18][19][20][21][22][23][24][25][26] Currently, the sensitivity and specificity of virtual cross-match analysis has undergone remarkable progression. Bub et al reported that the new EpHLA/EpVix method of virtual cross-matching has proved to be effective, feasible, fast, and capable of minimizing efforts on donor identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with immune-based refractoriness respond with higher corrected count increments when HLA-matched or antibody avoidance strategies are used, as compared to corrected count increments achieved after transfusing random single-donor platelets. [16][17][18] This highlights the importance of recognizing HLA antibodies in this patient population. If laboratories with no pretreatment miss antibodies due to the presence of an inhibitor, then platelets selected for these patients may be less effective.…”
Section: Discussionmentioning
confidence: 95%
“…The clinical importance of a missed specificity is also unknown. Patients with immune‐based refractoriness respond with higher corrected count increments when HLA‐matched or antibody avoidance strategies are used, as compared to corrected count increments achieved after transfusing random single‐donor platelets . This highlights the importance of recognizing HLA antibodies in this patient population.…”
Section: Discussionmentioning
confidence: 98%